Termite exocrine systems: a review of current knowledge - Costa-Leonardo, Ana Maria [UNESP]; da Silva, Iago Bueno [UNESP]; Laranjo, Lara Teixeira [UNESP] (Wiley, 2023)
In this review, we summarize the 22 exocrine glands hitherto described for termites (Isoptera), highlighting their distribution, morphological features, and likely function. The secretion from such glands displays a very important role in termite communication, but is also attributed to many other activities performed by these insects, including defense, building, and foraging, as well as physiological processes such as the synthesis of digestive enzymes, and antiseptic and lubricant compounds. Here, glands are divided into those associated with termite mouthparts and other head appendages, tegumentary glands with epithelial arrangement, those related to the reproductive apparatus, and glands which do not fit into these divisions. The exocrine systems in termites may be composed of classes 1, 2, and 3 secretory cells, which differ in how the glandular secretion is released. Moreover, they may exhibit a varied composition of secretory cell classes. Different glands may be involved in specific tasks and therefore produce specific compounds, although there are cases in which the same content is secreted by different glands, suggesting a functional plasticity. The chemical nature of these secretions and their role are well known for some glands, such as the frontal, salivary, tergal, and sternal ones. On the other hand, such aspects remain speculative or completely unknown for other glands. The number of termite exocrine glands is extremely low when compared to those described for eusocial Hymenoptera, and is a likely consequence of the higher diversity of species and chemical communication in the latter group. Moreover, vibroacoustic signals represent an important type of communication in termites. Further studies are encouraged to provide new insights into the occurrence and function of the exocrine systems in termites and how they modulate the different activities displayed by them.
Keywords: communication; defense; exocrine glands; feeding; Isoptera; morphology; pheromones; reproduction; secretion; secretory cells; semiochemicals; termites